2022
DOI: 10.23971/jefl.v12i2.4060
|View full text |Cite
|
Sign up to set email alerts
|

Short stories as an innovative EFL teaching technique to improve Pakistani elementary students’ English vocabulary

Abstract: Short stories are becoming very popular around the globe. Learning vocabulary, a crucial component of learning a foreign language, is at the heart of teaching a language and is important for language learners. The researchers believe that vocabulary plays a crucial part in learning any language. Therefore, it is crucial to look at the best strategies for enhancing vocabulary learning. With the aim of effectively utilizing short stories to improve vocabulary at the primary level, the current study was created t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The use of storytelling in classrooms continues to grow, and research demonstrates this method has many benefits for students for assisting them in learning new words in a memorable way and motivating them to participate in the classroom activities (Inal & Cakir, 2014). This finding is in line with the study conducted by Bhatti et al, (2022) implies that primary school English teachers should use short stories to increase their students' vocabulary. When a student listens to a story, not only are the vocabulary areas of the brain activated but also the sensory areas of the cortex as the topic is given life through story (Chow et al, 2014).…”
Section: Telling Stories As the Most Widely Used Activitiessupporting
confidence: 72%
See 1 more Smart Citation
“…The use of storytelling in classrooms continues to grow, and research demonstrates this method has many benefits for students for assisting them in learning new words in a memorable way and motivating them to participate in the classroom activities (Inal & Cakir, 2014). This finding is in line with the study conducted by Bhatti et al, (2022) implies that primary school English teachers should use short stories to increase their students' vocabulary. When a student listens to a story, not only are the vocabulary areas of the brain activated but also the sensory areas of the cortex as the topic is given life through story (Chow et al, 2014).…”
Section: Telling Stories As the Most Widely Used Activitiessupporting
confidence: 72%
“…Compared to meaning-focused input and meaning-focused output, which should be beyond the students' current level of proficiency, fluency development input and output should be within their current knowledge (Webb & Nation, 2017). Listening to stories as an example of fluency development is considered to enhance students' vocabulary (Inal & Cakir, 2014;Lin, 2014;Quy, 2017;Bhatti et al, 2022). Moreover, the 4/3/2 technique proves to be a successful technique in enhancing students' mastery of vocabulary.…”
Section: Fluency Developmentmentioning
confidence: 99%
“…The use of English stories was chosen because the researcher wanted to make learning fun yet meaningful. This is supported by the claim from (Slatterly & Willis, 2001) in (Bhatti et al, 2022) that short stories are effective and intriguing for igniting students' interest in learning. Besides, according to an empirical studies conducted by (Violetta-Irene, 2015), it is showed that using short stories in the EFL classroom is enjoyable for the students.…”
Section: Introductionmentioning
confidence: 75%
“…The six aspects of development aforementioned should be optimally developed by parents, teachers, and the environment. One of the aspects that should be developed earlier within early childhood's personal development is language (Supriatna & Wismaliya, 2019;Andriani, 2022;Bhatti et al, 2022). Through language, early childhood is able to interact among parents, family members, teachers, friends, classmates, and the environmental society.…”
Section: Introductionmentioning
confidence: 99%